Investigation on the homogeneity and stability of aqueous nano cellulose suspensions prepared using pluronic F-127 - Parveen, Shama (2015)
This paper presents the results of experimental investigation on the aqueous dispersion behaviour of micro crystalline cellulose (MCC) prepared using Pluronic F-127. For this purpose, different concentrations (0.5-3.0 wt.%) of MCC were dispersed in water with the help of ultrasonication technique using various concentrations of Pluronic F-127. The homogeneity of the suspensions and agglomerations were characterized by optical and transmission electron microscopy and the concentration of well dispersed MCC was measured using UV-Vis spectroscopy. Also, the suspensions were subjected to high speed ultracentrifugation at 3000 rpm and observed visually for sedimentation and subsequently, concentration was calculated using UV-Vis, in order to assess the long term stability of the suspensions. Based on these experiments, optimum concentration of Pluronic to disperse different MCC concentrations has been suggested.